2011
DOI: 10.1002/acp.1647
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, characteristics and functions of future‐oriented thoughts in daily life

Abstract: Despite the growing interest in future-oriented cognition in various areas of psychology, there is still little empirical data regarding the occurrence and nature of future-oriented thoughts in daily life. In this study, participants recorded future-oriented thoughts occurring in natural settings and rated their characteristics and functions. The results show that future-oriented thoughts occur frequently in daily life and can take different representational formats (more or less abstract), embrace various the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

30
272
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 372 publications
(334 citation statements)
references
References 36 publications
30
272
2
2
Order By: Relevance
“…Bearing in mind the essential role of AM and EFT in everyday life [16,40,55], the present findings suggest some clinical issues. In the first place, besides our MS patients' occasional complaints, the semi-structured interview showed that they were well (and accurately) aware of their difficulties and able to verbally articulate them to convey a clear message.…”
Section: Discussionmentioning
confidence: 97%
“…Bearing in mind the essential role of AM and EFT in everyday life [16,40,55], the present findings suggest some clinical issues. In the first place, besides our MS patients' occasional complaints, the semi-structured interview showed that they were well (and accurately) aware of their difficulties and able to verbally articulate them to convey a clear message.…”
Section: Discussionmentioning
confidence: 97%
“…Like memories for past events, many imagined future events are imbued with emotional value, referring either to positive situations that we would like to achieve or negative situations that we would rather avoid (D'Argembeau, Renaud, & Van der Linden, 2011). However, the extent to which such emotional anticipations are also organized in networks of related events is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…First, people frequently think about their personal future in abstract ways (e.g., by envisioning general goals and events; Anderson & Dewhurst, 2009;D'Argembeau, Renaud, & Van der Linden, 2011) and often access abstract knowledge about their future first when they attempt to imagine specific situations that might possibly happen to them (D'Argembeau & Mathy, 2011). Second, the construction of future event representations relies to a substantial extent on schematic knowledge (Berntsen & Bohn, 2010;Rubin, 2013).…”
Section: Introductionmentioning
confidence: 99%